Effect of Selective Cysteinyl Leukotriene Receptor Antagonists on Airway Inflammation and Matrix Metalloproteinase Expression in a Mouse Asthma Model - Chia-Hsiu Hsu; Chun-Ming Hu; Ko-Hsiu Lu; Shun-Fa Yang; Chung-Hung Tsai; Chun-Liang Ko; Hai-Lun Sun; Ko-Huang Lue (Pediatrics and Neonatology)
Cysteinyl leukotrienes (CysLTs) play a major role in the pathogenic changes of airway inflammation in asthma treatment. The matrix metalloproteinase (MMP) family, especially MMP-9 and MMP-2 levels, can reflect the status of airway remodeling. This study was undertaken to determine the role of a specific CysLT receptor antagonist in inhibition of airway inflammation and reversal of airway remodeling. Methods: Ovalbumin (OVA)-sensitized BALB/c mice were fed with a specific leukotriene receptor antagonist (MK-679), prednisolone or placebo from Days 15 to 27. Airway hyperreactivity, bronchoalveolar lavage fluid (BALF), and sera were analyzed. Pulmonary histology was obtained, and the levels of MMP-2 and MMP-9 in BALF were measured. Results: The OVA-sensitized mice developed significant airway inflammatory responses, including extensive eosinophils trafficking into BALF and lung interstitium, goblet cell hyperplasia, mucus hypersecretion, elevated serum immunoglobulin (Ig) E, and decreased level of serum IgG2a. Administration of MK-679 could reduce airway inflammation but was not as effective as prednisolone. However, MK-679 was more effective than prednisolone for reversing subepithelial fibrotic and myofibrotic reactions of airway remodeling. The levels of MMP-2 and -9 in BALF were proportional to the extent of airway remodeling, which can reflect the effects of treatment. Both prednisolone and MK-679 reverse airway hyperresponsiveness induced by OVA-sensitized mice. Conclusion: Cysteinyl leukotriene receptor plays a more important role than CysLT in the pathogenesis of allergic airway inflammation. MMP-2 and -9 may be more sensitive indicators of airway remodeling.